Do China's people favour redistribution? Evidence from an incentivized experiment. (25th January 2019) - He, Tai‐Sen; Putterman, Louis; Wang, Liangjun
Abstract: From 1949, China's leaders brought their country through three decades of income and wealth compression, which was followed by more than three decades of sharply rising inequality. What preferences do China's people hold regarding what price (if any) is worth paying for greater equality? We conduct a laboratory decision‐making experiment mimicking aspects of a macro‐political–economic environment, using Chinese undergraduate student subjects. We find that our subjects have qualitatively similar tastes for equality as their counterparts in parallel US and European experiments; for example, most are willing to sacrifice some payment for more equality of earnings among other participants, and their willingness to do this is stronger when inequalities originate randomly versus based on performance. Considering the cases permitting direct comparison between Chinese and US subjects' choices, redistributive choices tend to be a bit higher in China if the participant pays no direct cost and a bit lower if he or she pays such a cost, but the two distributions of decisions differ significantly in under 14% of conditions. Survey data too suggests preferences for a more equal income distribution in China than in other East Asian countries, suggesting a possible impact of the Chinese Communist Party dominance in education and media.